Meta-analysis of COVID-19 prevalence during preoperative COVID-19 screening in asymptomatic patients - Menno R Vriens; Ellen de Bock; Mando D Filipe; Milan C Richir; Roger K J Simmermacher; A Christiaan Kroese (BMJ Open)
Objectives Patients with COVID-19 may be asymptomatic and are able to transmit COVID-19 during a surgical procedure, resulting in increased pressure on healthcare and reduced control of COVID-19 spread. There remains uncertainty about the implementation of preoperative screening for COVID-19 in asymptomatic surgical patients. Therefore, this study aims to determine the prevalence of preoperative COVID-19, confirmed by reverse transcriptase PCR (RT-PCR), in asymptomatic patients.Design Systematic review and meta-analysis.Data sources Pubmed and Embase databases were searched through 20 February 2022.Eligibility criteria All COVID-19 articles including preoperative asymptomatic patients were included.Data extraction and synthesis Two independent reviewers extracted data and assessed risk of bias. Meta-analysis was performed to determine the prevalence of COVID-19 with 95% CI. Moreover, estimated positive predictive value (PPV), negative predictive value, false-positives (FP) and false-negatives were calculated for preoperative asymptomatic patients.Results Twenty-seven studies containing 27 256 asymptomatic preoperative screened patients were included, of which 431 were positive for COVID-19 by RT-PCR test. In addition, the meta-analysis revealed a pooled COVID-19 prevalence of 0.76% (95% CI 0.36% to 1.59%). The calculated PPV for this prevalence is 40.8%.Conclusions The pooled COVID-19 prevalence in asymptomatic patients tested preoperatively was 0.76%, with low corresponding PPV. Consequently, nearly three-quarters of postponed surgical procedures in asymptomatic preoperative patients may be FP. In the event of similar pandemics, modification of preoperative mandatory RT-PCR COVID-19 testing in asymptomatic patients may be considered.